Hmota, látka, hmotnost, tíha, váha: významné kategorie odborného dorozumění a imponderabilia obecného jazyka - Tulka, Jiří; Blažková, Iveta (Univerzita Pardubice, 1998)
An unignorable shift in the meaning of words, a partial or almost total transformation of literal meaning often happens in the transition between technical and colloquial language. The authors of this article take the separation of mental meaning from words to be the primary cause of this shift. Thus in many cases the words of an imponderable pattern arise.
Keywords: jazykověda; lexikologie; odborný jazyk; obecný jazyk; homonyma